Interactions - a law and religion podcast - Center for the Study of Law and Religion (2020)
"The INTERACTIONS podcast explores how law and religion interact in today’s world and throughout history. Since the first episode in 2020, this podcast routinely features interviews with leading scholars, previews of upcoming publications, and commentaries on pressing issues in the field. The Interactions podcast is produced by the Center for the Study of Law and Religion at Emory University."